The Danger of Ribā in The Perspective of Thematic Interpretation Qur’ān: An Analysis of Online Lending in Indonesia - Achmad Ichsanul Alaudin Iqbal; Kharis Nugroho (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study explores the dangers of riba in the perspective of thematic Quranic interpretation (tafsir maudhu’i), especially in the context of online loans in Indonesia. The research employs a qualitative literature-based method, analyzing hadiths and Qur'anic verses on ribā alongside data from contemporary Islamic economic literature. The results of the study indicate that ribā has destructive impacts such as damaging honor, plunging into poverty, bringing famine, and inviting punishment to a region. In the contemporary financial system, ribā is often found in conventional banking, interest-bearing credit, and online lending platforms that use an interest system and late fines. The widespread use of online lending services (pinjol) in Indonesia has caused significant economic and social problems. Weak regulations mean that many illegal lending platforms continue to operate and are difficult to eradicate, leaving consumers without adequate protection. One serious impact of this phenomenon is the misuse of personal data, where borrower information is often used for intimidation and pressure in the collection process. In addition, high default rates are a major problem, triggered by suffocating interest rates, unreasonable late fees, and low financial literacy. The consequences of online lending not only impact the economic aspects of individuals but also cause severe psychological distress, even in some cases leading to extreme actions such as suicide. As a solution, the study recommends the development of a syarī’ah-based financial system, public education about the dangers of ribā, and collaboration between the government and financial institutions to create fair economic policies that are in accordance with Islamic law.